Healthcare resource utilization by patients with treatment-refractory myasthenia gravis in England. (3rd July 2019) - Harris, Linda; Graham, Sophie; MacLachlan, Sharon; Exuzides, Alex; Jacob, Saiju
Abstract: Aims: To examine healthcare resource utilization associated with refractory myasthenia gravis (MG) in England. Materials and methods: This was a retrospective cohort study of linked data from the Clinical Practice Research Datalink and the Hospital Episode Statistics database collected between 1997 and 2016. Included patients were ≥18 years of age at the index MG diagnosis. Patients with refractory MG were identified using an algorithm based on treatments received. Healthcare resource utilization since the index date was compared between refractory and non-refractory cohorts. Results: The study included 1149 patients with MG, of whom 66 (5.7%) were refractory. Sex and age at diagnosis did not significantly differ between the refractory and non-refractory cohorts. Rates of healthcare resource utilization per person-year were significantly higher ( p  < .05) for patients with refractory compared to non-refractory MG for GP visits, visits to other healthcare professionals, outpatient visits and inpatient hospitalization. Patients in the refractory cohort spent more total days hospitalized since the index visit than patients in the non-refractory cohort (median, 33 vs. 16 days [ p  < .0001]). Limitations: The algorithm for identifying refractory patients did not include clinical criteria. Also, treatments administered in hospitals or by specialists were not available in the databases. Conclusions: Patients in England with refractory MG more often visit healthcare providers, are hospitalized and visit an emergency room than patients with non-refractory MG.